การพัฒนาผลิตภัณฑ์ไส้กรอกจากพืช - ภานุวัฒน์ พงศ์ศรีเพียร (จุฬาลงกรณ์มหาวิทยาลัย, 2019)
In the process of livestock farming for human consumption, it creates the pollution to damage the environment. This also consumes the large amount of agricultural area, water and natural resources. Vegetarian food is one of the alternative choices to help preventing human-made pollution. In addition, people are increasingly interested in vegan food and the vegan food market has significantly grown over the last few years. Nowadays, sausage has become one of the most popular food in the market. Unfortunately, meat sausage contains high saturated fatty acid and cholesterol which cause obesity, cardiovascular disease and increase the risk of cancer. This study aims to develop the plant-based sausage using all plant ingredients (meat-free), including pea protein, rice protein, rice bran oil, canola oil. That is rich in omega-3 and healthier nutrition value than meat product because of its fat content is lower by 70%. In this study, the plant-based sausage was determined the effect of 3 different protein ratios, which are Pea protein 100% (Pea100), Pea protein 50% and Rice protein 50% (Pea50Rice50) and Rice protein 100% (Rice100), on textural parameters, water activity (aw) and color parameter (L*, a* and b*) compared with the commercial meat control sample and vegan control sample. The results showed that there was no significant difference (p<0.05) of hardness among the treatments. The Pea100 sample had no significant difference (p<0.05) in firmness and adhesiveness in comparison with commercial vegan control sample. Moreover, the Rice100 showed no significant difference (p<0.05) in aw compared with meat control sample and vegan control sample. Considering color parameters, the inclusion of rice protein resulted in an increase of L*, a* and b*.